The Double Jeopardy of Feeling Lonely and Unimportant: State and Trait Loneliness and Feelings and Fears of Not Mattering - McComb, Sarah E.; Goldberg, Joel O.; Flett, Gordon L.; Rose, Alison L. (Frontiers in Psychology, 2020)
There have been recent concerns about an “epidemic of loneliness” during the pandemic, given the pervasiveness of loneliness in the population and its harmful effects on health and well-being. Therefore, it is important to establish the correlates of loneliness. The purpose of the current study was to explore how loneliness relates to a construct termed mattering, which is the feeling of being important to other people. Mattering was assessed with multiple measures in the current study (e.g., mattering in general, fears of not mattering, and mattering to peers). A sample of 172 female psychology undergraduate students aged 18-25 years completed self-report measures of general mattering, mattering to peers, anti-mattering, fear of not mattering, and state and trait loneliness. As predicted, lower levels of both general mattering and mattering to peers were associated with higher state loneliness. Higher feelings of anti-mattering (feelings of being invisible and insignificant to others) and fears of not mattering were associated with greater trait loneliness, as well as a reduced sense of mattering to friends. The findings illustrate that feeling as though one does not matter to others (i.e., feeling insignificant and unimportant) is associated with increased state and trait loneliness among young women. Implications are discussed for loneliness theory and how these results can enhance both clinical understanding and practice